2020
DOI: 10.1111/ped.14275
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for motor coordination problems in preschool‐age children

Abstract: Background: Motor coordination problems (MCP) in children can sometimes be diagnosed as developmental coordination disorder. Early intervention for developmental coordination disorder is necessary because it often continues into adolescence, causing mental and physical complications. Few studies have investigated the prevalence of childhood MCP in the Japanese population, examining the risk factors for MCP. We therefore investigated the prenatal factors associated with MCP in preschool-age children. Methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(70 reference statements)
1
6
0
2
Order By: Relevance
“…We found that both SGA and smoking were independently associated with increased DCD risk, although in different domains, with only smoking affecting Control during Movement. These findings are consistent with previous research showing a relation between antenatal smoking and motor difficulties, 17 even when cotinine markers were used 18,20 and when socio‐economic factors and alcohol intake were taken into account 19 56 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that both SGA and smoking were independently associated with increased DCD risk, although in different domains, with only smoking affecting Control during Movement. These findings are consistent with previous research showing a relation between antenatal smoking and motor difficulties, 17 even when cotinine markers were used 18,20 and when socio‐economic factors and alcohol intake were taken into account 19 56 …”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous research showing a relation between antenatal smoking and motor difficulties, 17 even when cotinine markers were used 18,20 and when socio-economic factors and alcohol intake were taken into account. 19 Cigarette smoke contains several harmful substances that can cross the placenta and affect the child prenatally. 56 Nicotine binds to receptors of several organs, including the brain.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Hokkaido birth cohort, for developmental disorder symptoms, active maternal smoking, as determined by the levels of maternal plasma cotinine, contributed to an increased risk in a child’s total difficulties and hyperactivity/inattention at a pre-school age [ 56 ]. Smoking during pregnancy was also the main factor associated with motor coordination problems in preschool-aged children [ 57 ]. As described in subsection “ Prenatal chemical exposure, birth size, growth, and cord adiponectin and leptin as predictors ”, the association between the decreased hyperactivity/inattention and increased leptin suggested that cord blood adipokines may be a predictor of hyperactivity/inattention problems at a preschool age [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Japanese version of the Developmental Coordination Disorder Questionnaire is an adaptation of the original Questionnaire, performed according to international guidelines for translation of clinical tools, to adapt to the Japanese culture. 12,13,16 The questionnaire is comprised of three subscales, as follows: control during movement, six items; fine motor and handwriting, four items; and general coordination, five items. 7,12 Each item is assessed on a five-point scale, with a lower score indicative of a more severe developmental coordination disorder trait.…”
Section: Study Samplementioning
confidence: 99%